MODIFIED FEEDING BOTTLE FOR INFANT WITH CLEFT LIP AND PALATE AT THE PERIPHERAL AREA: A CASE REPORT - Mardiyantoro, Fredy; Hapsari, Diwya Nugrahini; Milla, Lalita El (Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2019)
Introduction:A newborn can suck at breast and latch well to get breast milk, but infants born with cleft lip and palate have difficulties to press the nipple by their tongues towards palatal direction. Case:A 10-day-old female infant came with complaint of not being able to breastfeed from a normal bottle and accordingly need to use spoon for milk feeding. She was planned to perform first step operation at 3 months with minimum 10 pounds of body weight. For nutrient intake, nasogastric tube had been placed on the patient. Case management :At the first visit, impression procedure was performed using red wax material that previously warmed thus it can be shaped according to the defect on infant’s palate. Subsequently, feeding obturator was fabricated using the resulting cast. Fabrication of feeding obturator used putty impression material combined with feeding bottle nipple. Thereafter, the modified feeding bottle was tried in the patient’s mouth. Conclusion:the use of putty material combined with feeding bottle nipple in infants with cleft palate may function as obturator. Furthermore, correction using the one of the modified feeding bottle can be carried out every 1-2 weeks until surgical repair of the cleft palate is performed.Keywords: cleft palate, feeding bottle, putty material, nutrition